Linked Data: what happens to heterogeneity and interoperability - Herrera Cubides, Jhon Francined; Gaona García, Paulo Alonso; Sánchez Alonso, Salvador (Scientia et Technica, 2018)
Linked Data – LD, allows the construction of the Web of Data, which use basic principles that contribute to the growth of the Web. The process developed by LD faces different scenarios that seem to limit the linking process. This paper exposes the problems of heterogeneity, interoperability and data quality, as factors that restrict the process of data linkage. For this, the methodological design performs a bibliographic exploration; the results examine and discuss the postures about the mentioned problems, and the possible incidence of these in the quality of the linked data. In conclusion, speaking about heterogeneity is intrinsic, since the information will always be heterogeneous. Data models may be different but if the data format is common, interoperability is possible. Data models must be known and public, in order to avoid problems that prevent the development of the Web Data.